‘Sensory pad’- A novel chemoreceptive device in Hilsa (Tenualosa ilisha) to support its amphihaline attribute - Chatterjee, Subhendu Kumar; Malick, Chandan; Bhattacharya, Samir; Kundu, Rakesh; Suresh, Vettath Raghavan; Saikia, Surjya Kumar (Acta Biologica Szegediensis, 2018)
Hilsa, Tenualosa ilisha is an amphihaline migratory fish that performs spawning migration to selected freshwater rivers in Indo-Pacific region. It is not clear what force triggers its migration. In this paper, we attempted to describe the features of outer integument from its head region as chemosensory site which appears to play significant role in its upstream migration. We found that this area (termed as snout) has very soft and scale less tissue oriented with pit like grooves named as ‘epidermal pit’. Around these pits, odorant receptor G-protein subunits (Gαq, Gαs/olf and Gαo) have been substantially localized. Use of DASPEI also traced this area with neuronal existence. These features in the snout likely to contribute for chemosensory requirements of the fish during upstream migration. Considering such findings, we named this area of snout as ‘sensory pad’. Its position at the forefront of olfactory organ and brain may have important role in facilitating sensory reception by the fish swimming upstream to the river.